Population dynamics of Musca domestica (Diptera: Muscidae): experimental and theoretical studies at different temperatures - Tardelli, Carina Aparecida [UNESP]; Godoy, Wesley Augusto Conde [UNESP]; Mancera, Paulo Fernando Arruda [UNESP] (Brazilian Archives of Biology and Technology, 2004)
Neste estudo a dinâmica populacional de M. domestica foi avaliada em duas temperaturas, 20ºe 30ºC. A dinâmica foi modelada utilizando um modelo de crescimento populacional dependente da densidade. As temperaturas investigadas no estudo não produziram mudança qualitativa em termos de comportamento dinâmico, ou seja, a dinâmica populacional de M. domestica foi caracterizada por um equilíbrio estável em ambas as temperaturas. Entretanto, o ponto de equilíbrio foi influenciado pelos resultados obtidos nas diferentes temperaturas. A diferença entre os autovalores obtidos nas duas temperaturas foi a provável causa da diferença entre os pontos de equilíbrio. As implicações destes resultados para a dinâmica populacional de M. domestica são discutidas.

In the present study, the population dynamics of M. domestica was evaluated at two different temperatures, 20 and 30ºC. The dynamics was modeled using a density-dependent model of population growth. The temperatures investigated in this study produced no qualitative change in terms of dynamic behaviour, i. e. the population dynamics of M. domestica was characterized by a stable equilibrium at both temperatures. However, the steady state was influenced by the results obtained at different temperatures. The difference between the eigenvalues obtained at the two temperatures was probably the cause of the difference between the distinct steady states. The implications of these results for the population dynamics of M. domestica are discussed.
Keywords: Population dynamics; Musca domestica; density-dependent model; temperature